Processo de trabalho e cargas intervenientes no trabalho de enfermeiros captadores de órgãos e tecidos para transplante - Pedrosa, Sara de Almeida (2023)
The health-disease process is conditioned per many factors denominate social determinants of health, with emphasis for work. During the work, the worker is exposed the many workloads what result in physical and psychological exhaustion. It is known that the nursing work it is precarious conditions that generate exhaustion and disease, being important the understanding this process in areas insufficiently studied for science, with the nurse that work process with tissue and organ procurement. Objective: Understanding the health-disease process of the nurses that working with tissue and organ procurement and identify the workload which nurses are exposed. Method: Descriptive-exploratory study, qualitative, developed at state of São Paulo with nurses that work in tissue organ donation committees for transplantation. The data collection happen by means of individual interview guided by predefined questions for further content analysis. Results: The nurse was identified as an agent of the work process, which has a specific object to the health care needs of potential organ donors and recipients. In addition to specific instruments, which are not used in other areas of health and nursing, to achieve the purpose of the work: obtaining healthy organs and tissues for an effective transplant. It was found that most of the study participants are new, in relation to age, time of training and performance in the Commission and lack specific training to work in organ donation and transplantation. Most of the interviewees do not work exclusively with the Commission, as they are inserted in scenarios marked by the accumulation of functions and work overload. Participants identified the following workloads: physiological, psychic and biological. Conclusions: It is important to emphasize the need for training to exercise the function and provide opportunities for exclusive positions at Donation and Transplantation Commission. The identification of workloads can subsidize actions in worker health to minimize exposure and mitigate wear processes.